Systematic Literature Review: A Framework of the Influence of Human Resource Management Practices on the Performance of Micro, Small, and Medium-Sized Enterprises through Innovative Work Behaviour - Abdulloh Abdulloh; Sudarmiatin Sudarmiatin; Agus Hermawan (Harmony Management: International Journal of Management Science and Business, 2025)
This study conducts a Systematic Literature Review to examine the relationship between job enrichment, the Human Resource Information System, and work–life balance on organisational performance through the mediating role of innovative work behaviour, with a particular focus on medium-scale Micro, Small, and Medium-Sized Enterprises. Drawing on Scopus-indexed publications from 2020 to 2025, the review identifies theoretical and empirical findings that highlight the importance of human resource practices and digital transformation in strengthening organisational innovation. The analysis reveals that job enrichment significantly enhances employee autonomy, engagement, and intrinsic motivation, which in turn fosters innovative work behaviour. Likewise, the Human Resource Information System contributes to performance improvement by increasing decision-making efficiency and supporting data-driven innovation processes. Meanwhile, work–life balance promotes creativity and reduces stress, thereby fostering an environment conducive to innovative thinking. Furthermore, innovative work behaviour is found to mediate the relationship between human resource practices and organisational performance by transforming individual innovation into collective organisational outcomes. These findings indicate that integrating the Human Resource Information System with job enrichment and work–life balance policies can substantially enhance the competitiveness and productivity of medium-scale Micro, Small, and Medium-Sized Enterprises. This study contributes to theoretical advancement in innovation-oriented human resource management and offers practical implications for developing adaptive human resource systems to ensure sustainable business performance in the digital era.